2017
DOI: 10.1016/j.maturitas.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment at baseline is associated with future poor physical functioning among middle-aged women: The Study of Women’s Health Across the Nation, Michigan Site

Abstract: Objectives Emerging evidence suggests that the prevalence rates of poor functioning and of disability are increasing among middle-aged individuals. Visual impairment is associated with poor functioning among older adults but little is known about the impact of vision on functioning during midlife. The objective of this study was to assess the impact of visual impairment on future physical functioning among middle-aged women. Study design In this longitudinal study, the sample consisted of 483 women aged 42 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The present findings are in line with previous studies that have shown that older people with visual impairment have worse levels of physical functioning than those with normal vision, using less practical measures of functioning (e.g. an obstacle course or a battery of fitness tests) and smaller samples [3,[14][15][16]. The present study adds to this literature by showing that people with visual impairment have slightly worse levels of handgrip strength which can consequently be associated with lower physical functioning.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings are in line with previous studies that have shown that older people with visual impairment have worse levels of physical functioning than those with normal vision, using less practical measures of functioning (e.g. an obstacle course or a battery of fitness tests) and smaller samples [3,[14][15][16]. The present study adds to this literature by showing that people with visual impairment have slightly worse levels of handgrip strength which can consequently be associated with lower physical functioning.…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have explicitly tested the association between visual impairment and physical performance in older age, but those that have indicate decrements among those with poor vision. One study of middleaged women (n=483, age 42-56 years) observed poorer performance on a battery of tests (including a 40-foot timed walk, timed stair climb and forward reach) in women with impaired vision over 10-year follow-up [14]. Similarly, a study of 6,112 women aged 69 and older reported an association between visual impairment and functional decline [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence has identified VI as a marker of poor physical functioning over 10 years. 49 However, adults who were physically active have been found to have a lower cumulative incidence of VI, which could suggest behavioral impacts on vision outcomes. 50 Longitudinal and interventional studies are needed to further understand the direction of such associations and whether the prevention of physical limitations can be accomplished through vision correction.…”
Section: Discussionmentioning
confidence: 99%
“…Vision impairment (VI) affects 191 million people globally, mostly due to treatable or preventable causes [1]. VI is associated with a wide range of adverse outcomes including poor quality of life, worse functioning and detrimental impact on mental health [2,3,4,5,6]. Vision screening is an important public health measure to address the burden of VI.…”
Section: Introductionmentioning
confidence: 99%
“…Space and lighting requirements for testing vision are factors limiting the use of conventional vision testing methods in non-eye care settings. The Titmus vision screener is an instrument that is widely used in these situations, given its portability and ease of use [6,7]. It is a vision screening device with optically simulated distance and near vision settings and has built -in lighting for vision testing.…”
Section: Introductionmentioning
confidence: 99%